Numerical Solution of Steady-State Free Boundary Problems Using the Singular Boundary Method (Advances in Applied Mathematics and Mechanics, 2020)
In this paper, the recently-developed singular boundary method is applied to address free boundary problems. This mesh-less numerical method is based on the use of the origin intensity factors with fundamental solutions. Three numerical examples and their results are compared with the results obtained using traditional methods. The comparisons indicate that the proposed scheme yields good results in determining the position of the free boundary.